Economic Behavior of Anchovy Fishermen in Maintaining Their Business and Income Risk in Tlanakan District, Pamekasan Regency - M. Alivi Aziz; Teguh Soedarto; Endang Yektiningsih (Universitas KH. Abdul Chalim Mojokerto, 2025)
Anchovy fishermen in Tlanakan District, Pamekasan Regency, contribute significantly to the local economy, but face challenges in the form of weather fluctuations, price instability, and technological limitations. This study aims to analyze the economic behavior, social status, and income risk of fishermen using a quantitative approach with indicators of risk preference, time preference, technology adoption, culture, sea experience, education level, and age. Income risk is analyzed through the coefficient of variation. The results show that fishermen prefer to catch anchovies because of the low risk and stability of the catch. Traditional technology still dominates, although modern technology has the potential to increase productivity. Socially, more than 10 years of experience at sea and a higher level of education have been shown to contribute positively to income. However, uncertainty due to weather changes remains a major obstacle.